Geographic and intrapopulational variation in colour and patterns of an aposematic toad, Melanophryniscus rubriventris (Amphibia, Anura, Bufonidae) - Bonansea, Maria Ines (2012)
The aposematic toad genus Melanophryniscus is a polymorphic group with noticeable variation in colour and pattern. Here, we objectively evaluate variation in spectral reflectance and quantify variation in patterning within and among populations of the species M. rubriventris in NW Argentina. We conducted spectrophotometric analysis on 69 individuals and recorded dorsal and ventral pattern morphs of 727 individuals from six populations. We found high divergence in the reflectance spectra, the extent of brightly coloured areas, and the skin alkaloid profiles with no correlation among coloration varieties, alkaloid profiles, and the geographic distance between populations. Our analyses imply subdivision of sampled populations groupings based mostly on different dorsal colorations. Our results also reveal that populations with very similar patterns may differ markedly in colour and vice versa. It is striking that these aposematic toads show a pronounced variation in colour and patterning among and within populations showing individuals with a conspicuous bright dorsal colouration but also morphs with a rather cryptic black or drab colouration. However, the known presence of several alkaloids classes in all populations suggests that all morphs might be equally unpalatable.